Ultrasound Imaging for Ovarian and Deep Infiltrating Endometriosis - Exacoustos, Caterina; Zupi, Errico; Piccione, Emilio (Seminars in Reproductive Medicine, 2017)
The main challenges of imaging for endometriosis are the detection of nonovarian disease and the evaluation of the extension of the disease into pelvic structures. Transvaginal ultrasonography (TVS) has been proposed as the first-line imaging technique because it allows extensive exploration of the pelvis. The “typical” endometrioma is a unilocular cyst with homogeneous low-level echogenicity (ground glass echogenicity) of the cyst fluid. The use of color Doppler helps avoid classifying malignancies as endometriomas, defining the presence of vascular flow in papillations. The real-time dynamic TVS examination of adhesions and pouch of Douglas (POD) obliteration, using the sliding sign technique, seems to be useful in the identification of women at increased risk for bowel endometriosis. Transvaginal ultrasound allows an accurate assessment of the vagina, particularly the areas of the posterior and lateral vaginal fornixes, the retrocervical area with torus uterinum and uterosacral ligaments, and the rectovaginal septum. The slightly filled bladder permits an evaluation of the bladder walls and the presence of endometriotic nodules which appear as hypoechoic linear or spherical lesions bulging toward the lumen, involving the serosa, muscularis, or (sub)mucosa of the bladder. Deep nodules of the rectum appear as hypoechoic lesions, linear or nodular retroperitoneal thickening with irregular borders, penetrating into the intestinal wall distorting its normal structure with the presence of few vessels observed with power Doppler evaluation. Adenomyosis can be observed with the two-dimensional (2D) TVS showing the typical myometrial features and 3D evaluation of the junctional zone. Although the sensitivity and specificity of TVS in the prediction of deeply infiltrating endometriosis and adenomyosis is high, their assessment by TVS is difficult and needs a great expertise.
Keywords: deep infiltrating endometriosis; transvaginal ultrasound; endometrioma, adenomyosis; 3D ultrasound; bladder endometriosis; rectal endometriosis